"He doesn't really have bipolar ...". The rise of strategic essentialism and diagnostic possessiveness in bipolar disorder - Rhiannon Lane (Elsevier, 2024)
Bipolar disorder has risen in prominence in recent years, arguably in part through its association with various celebrities and positive related attributes such as creativity. The category itself has also widened with increasing numbers seeking out the diagnosis. Drawing upon observations of a psychoeducation programme for bipolar disorder and semi-structured interviews with those diagnosed, this paper considers the role of diagnostic prestige and essentialism in shaping identificatory practices surrounding bipolar disorder. The data suggests that bipolar comes to fulfil a meaningful explanatory role for participants, providing an important sense of group belonging and identity.This tendency to positively relate to bipolar in order to promote social cohesion and positive self-understandings is linked to the practice of 'strategic essentialism' (Spivak, 1990; Voronka, 2017), whereby category homogeneity is emphasised. The benefits associated with the diagnosis arguably encourage boundary making and homogenisation in order to prevent category dilution and loss of meaning. As such, while essentialism can be helpful in maintaining group cohesion, it is also associated with diagnostic possessiveness, whereby individuals undermine the diagnostic claims of others, creating divisions between those with and without the diagnosis.